Association of the missense variant p.Arg203Trp in PACS1 as a cause of intellectual disability and seizures. Issue 2 (23rd January 2017) - Stern, D.; Cho, M.T.; Chikarmane, R.; Willaert, R.; Retterer, K.; Kendall, F.; Deardorff, M.; Hopkins, S.; Bedoukian, E.; Slavotinek, A.; Schrier Vergano, S.; Spangler, B.; et al.
Abstract : Graphical abstract key: ADHD, attention deficit hyperactivity disorder; ASD, atrial septal defect; DD, developmental delay; EEG, electroencephalogram; Ht, height; ID, intellectual disability; OCD, obsessive‐compulsive disorder; OFC, open fontanelle; PDA, patent ductus arteriosis; PFO, patent foramen ovale; VSD, ventricular septal defect; Wt, weight.